2021
DOI: 10.1111/spsr.12461
|View full text |Cite
|
Sign up to set email alerts
|

Popular Attitudes Toward the Distribution of Vaccines Against COVID‐19: The Swiss Case

Abstract: With the arrival of vaccines against the novel coronavirus in late 2020, the issue of how vaccines should be distributed and which groups should be prioritized has become salient. We study popular attitudes toward the distribution of COVID‐19 vaccines and how these have changed over the course of the pandemic in Switzerland, drawing on data from two rounds of an original public opinion survey conducted in the spring and winter of 2020. We find that the public supports prioritizing vulnerable groups such as hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…This finding suggests that the public prefers those who are most likely to be severely impacted by an infection, and those who are most needed to mitigate the most adverse effects of the pandemic on the country. This is largely line with expectations based on utilitarian principles as well as with recent evidence from other studies (Duch et al, 2021;Gollust et al, 2020;Knotz et al, 2021a;Luyten et al, 2022;Persad et al, 2020;Reeskens et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding suggests that the public prefers those who are most likely to be severely impacted by an infection, and those who are most needed to mitigate the most adverse effects of the pandemic on the country. This is largely line with expectations based on utilitarian principles as well as with recent evidence from other studies (Duch et al, 2021;Gollust et al, 2020;Knotz et al, 2021a;Luyten et al, 2022;Persad et al, 2020;Reeskens et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings complement evidence from previous studies on vaccine prioritization preferences (Ceccato et al, 2021 ; Duch et al, 2021 ; Gollust et al, 2020 ; Knotz et al, 2021a ; Luyten et al, 2022 ; Persad et al, 2021 ; Reeskens et al, 2021 ; Schaeffer and Haderup Larsen, 2022 ), by highlighting that the public’s prioritization preferences are not only remarkably consistent across the five countries we study, but also within each country, and suggesting low levels of polarization about who should be prioritized for COVID-19 vaccination.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent empirical literature has explored public preferences for the allocation of COVID-19 vaccines. A majority of these studies examined public opinion on prioritisation within high-income countries and when COVID-19 vaccine availability was still heavily constrained in those countries ( Duch et al, 2021 ; Gollust et al, 2020 ; Knotz et al, 2021 ; Luyten et al, 2020 ; Persad et al, 2021 ; Reeskens et al, 2021 ; Sprengholz et al, 2021 ). Based on data from online surveys and survey experiments, the studies revealed substantial public support for prioritising frontline healthcare workers and clinically vulnerable groups ( Duch et al, 2021 ; Persad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A majority of these studies examined public opinion on prioritisation within high-income countries and when COVID-19 vaccine availability was still heavily constrained in those countries. (Duch et al, 2021; Gollust et al, 2020; Knotz et al, 2021; Luyten et al, 2020; Persad et al, 2021; Reeskens et al, 2021; Sprengholz et al, 2021) Based on data from online surveys and survey experiments, the studies revealed substantial public support for prioritising frontline healthcare workers and clinically vulnerable groups. (Duch et al, 2021; Persad et al, 2021) To our knowledge, only four studies to date have examined individuals’ preferences on the distribution of COVID-19 vaccines across national borders.…”
Section: Introductionmentioning
confidence: 99%